How to treat urinary incontinence in women without surgery? - Huang WL (Archive of Urological Research - Peertechz Publications, 2020)
Statement of the problem: Urinary incontinence is defined as the loss of bladder control. In Western medicine, the treatment is hard to achieve and the need of surgery is common. In Traditional Chinese Medicine (TCM), urinary incontinence is caused by Kidney Yang deficiency.  Purpose: To demonstrate it is possible to treat urinary incontinence, without the need of surgery.  Methods: A case report of 55-years-old female patient, with urinary incontinence for around 30 years. After three years of the birth of her third and last child, all delivered by vaginal births, the symptoms appeared when she would sneeze or cough and worsened, requiring diapers for performing different activities, mainly when she had contact with water in her feet. Her gynecologist recommended her for surgery, but she refused for a long time and after years, she tried another treatment. She was diagnosed with Kidney-Yang deficiency and Blood deficiency according to TCM. She performed the procedure of radiesthesia, which resulted in level 1 of 8 in energy, the minimum possible. She started Chinese dietary therapy, auricular acupuncture, apex ear bloodletting, moxibustion.  Findings: She had complete improvement of the symptoms in three Chinese dietary therapy, sessions of acupuncture, homeopathy and crystal-based medication, not needing to use diapers or sanitary pats anymore.  Conclusion: Based on this case report, we conclude that it is possible to treat urinary incontinence without surgery. To this aim, we need to see the patient as a whole, considering the energy imbalances, which were causing urinary incontinence, using Chinese Nutritional Therapy, acupuncture, moxibustion, homeopathy and crystal-based medications.